Pengaruh Nadwah Usbu’iyyah terhadap Peningkatan Penguasaan Kaidah Bahasa Arab Mahasiswa Pendidikan Bahasa Arab IAIN Palopo. - Annisa Zahra Jabbar; Mawardi; Putra, H. Alfan (Universitas KH. Mukhtar Syafaat, 2025)
In learning Arabic, students of the Arabic language education program at the Islamic State Institute of Palopo cannot be separated from the factors that make learning Arabic challenging. This research examines the impact of the